Airway management during in-hospital cardiac arrest (IHCA) in adults: UK national survey and interview study with anaesthetic and intensive care trainees - Goodwin,L; Samuel,K; Schofield,B; Voss,S; Brett,S; Couper,K; Gould,D; Harrison,D; Lall,R; Nolan,J; Perkins,G; Soar,J; et al. (Journal of the Intensive Care Society, 2021)
Background: The optimal airway management strategy for in-hospital cardiac arrest (IHCA) is unknown.Methods: An online survey and telephone interviews with anaesthetic and intensive care trainee doctors identified by the United Kingdom (UK) Research and Audit Federation of Trainees. Questions explored IHCA frequency, grade and specialty of those attending, proportion of patients receiving advanced airway management, airway strategies immediately available, and views on a randomised trial of airway management strategies during IHCA.Results: Completed surveys were received from 128 hospital sites (76% response rate). Adult IHCAs were attended by anaesthesia staff at 40 sites (31%), intensive care staff at 37 sites (29%), and a combination of specialties at 51 sites (40%). The majority (123/128, 96%) of respondents reported immediate access to both tracheal intubation (TI) and supraglottic airways (SGAs). A bag-mask technique was used ‘very frequently’ or ‘frequently’ during IHCA by 111/128 (87%) of respondents, followed by SGAs (101/128, 79%) and TI (69/128, 54%). The majority (60/100, 60%) of respondents estimated that ≤30% of IHCA patients undergo TI, while 34 (34%) estimated this to be between 31-70%. Most respondents (102/128, 80%) would be ‘likely’ or ‘very likely’ to recruit future patients to a trial of alternative airway management strategies during IHCA. Interview data identified several barriers and facilitators to conducting research on airway management in IHCA.Conclusions: There is variation in airway management strategies for adult IHCA across the UK. Most respondents would be willing to take part in a randomised trial of airway management during IHCA.